Diagnosis of Splenic Lymphoma by Endoscopic Ultrasound Guided Fine Needle Aspiration: A Case Report and Review of the Literature - Umar Darr; Zubair Khan; Muhammad Ali Khan; Anas Renno; Turki Alkully; Sehrish Kamal; Tariq Hammad; Yaseen Alastal; Muhammad Imran Khan; Ali Nawras (Case Reports in Gastrointestinal Medicine)
Introduction. Splenic tumor is usually found as an incidental finding on CT of abdomen. Traditionally, ultrasound (US) or computed tomography (CT) guided biopsies were employed for the purpose of sampling; however they have been reported to have a complication rate of 5.3%. Endoscopic ultrasound-fine needle aspiration (EUS-FNA) has been recently utilized for the purpose of sampling splenic tumors. In literature there are 7 reported instances where splenic lymphoma was diagnosed using EUS-FNA. We present a case of follicular B cell lymphoma of the spleen diagnosed using EUS-FNA. Case Report. 58-year-old female presented to her primary care physician for left upper quadrant abdominal pain for one week. Physical exam was significant for left upper quadrant tenderness. Her laboratory tests were within normal limits. She underwent CT scan of abdomen which revealed approximately 5 cm × 5 cm mass in spleen. EUS-FNA of the spleen revealed a large hypoechoic, heterogeneous, well-demarcated mass measuring 54.7 mm × 43.0 mm. Fine needle aspiration was performed, and the sample was submitted for cytology and flow cytometry. Flow cytometry revealed a lambda monotypic population of B cells displaying dim CD19 and CD10. Diagnosis of B cell non-Hodgkin low grade follicular lymphoma was made. Conclusion. Endoscopic ultrasound with fine needle aspiration is a very rare but safe, reliable method of diagnosis of splenic lymphomas.